(untitled) (Medico Legal Update, 2020)
We report here an autosomal STR DNA database of Population of Madhya Pradesh and evaluation of autosomal STR diversity in the context of population genetics and forensic efficiency parameters. In this study, Allele frequencies of 15 autosomal STR loci were investigated in 123 unrelated individuals (57 Female & 66 Male) from the various geographical regions of Madhya Pradesh using PowerPlex® 16 HS System. All the studied loci appeared the high degree of genetic polymorphism with observed Heterozygosity (Ho= observed heterozygosity) ranged from 0.911 (D21S11) to 0.659 (TPOX). Locus PENTA E showed the highest power of discrimination (0.978) and the highest polymorphism (PIC = 0.90). The combined probability of match (CPM) and combined paternity Index (CPI) for all the 15 STR loci was found to be 2.8 x 10-18 and 1.2 x106, respectively. The combined discrimination power (CPD) and combined exclusion power (CPE) for all the tested 15 Loci was observed 1 and 0.9999989 respectively, assign that all the loci are highly polymorphic and have the potential for forensic application.